2003
DOI: 10.1097/00005537-200304000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Head and Neck in Ontario, Canada, and in Southeastern Norway

Abstract: The results of treatments, based on different overall treatment polices, for all patients were similar. The differences in recorded T category with no statistical difference in overall survival suggest a difference in staging assignment and raises a question about the reliability of the TNM staging process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
2
10
2
Order By: Relevance
“…The overall survival at 5 years was 26% and the authors chose to report disease‐free survival not disease‐specific survival as their major outcome. Their TNM stage case mix appears to be more severe than both our series and the Hoffman survey and could reflect true differences, stage migration, different staging rules, different investigations or the poor reliability of TNM 20 …”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The overall survival at 5 years was 26% and the authors chose to report disease‐free survival not disease‐specific survival as their major outcome. Their TNM stage case mix appears to be more severe than both our series and the Hoffman survey and could reflect true differences, stage migration, different staging rules, different investigations or the poor reliability of TNM 20 …”
Section: Discussioncontrasting
confidence: 57%
“…Their TNM stage case mix appears to be more severe than both our series and the Hoffman survey and could reflect true differences, stage migration, different staging rules, different investigations or the poor reliability of TNM. 20 Eckel et al 6 reported a series of 228 consecutive cases treated a single institution in Germany. The mean age was 53, which is much younger than other series.…”
Section: Comparisons With the Literaturementioning
confidence: 99%
“…Likewise, treatment was withheld when patients were considered mentally unfit for treatment. The percentage of patients excluded (7.9%) from treatment in this study is similar to that previously reported from a comparable institution in Canada [7]. As life expectancy increases, clinicians increasingly face the challenge of treating elderly patients with cancer, including some types of head and neck carcinomas [8].…”
Section: Discussionsupporting
confidence: 81%
“…The information is entered by a records technologist into the Head & Neck file of the MEDLOG Clinical Database System [10]. The information in this prospective database has been the data source for numerous publications [11][12][13][14][15], and for this study provides an opportunity for a unique audit of the data elements within the OCR that are important to researchers in clinical oncology.…”
Section: Introductionmentioning
confidence: 99%